2017
DOI: 10.3748/wjg.v23.i19.3480
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of microRNA target genesIL12B,INSR,CCND1andIL10in gastric cancer

Abstract: AIMTo evaluate associations between miRNA target genes IL12B, INSR, CCND1 and IL10 polymorphisms and gastric cancer (GC) in European population.METHODSGene polymorphisms were analyzed in 508 controls and 474 GC patients from 3 tertiary centers in Germany, Lithuania and Latvia. Controls were patients from the out-patient departments, who were referred for upper endoscopy because of dyspeptic symptoms and had no history of previous malignancy. Gastric cancer (GC) patients had histopathological verification of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The possible role of different genetic alterations in the development of gastric cancer has been studied [ 13 , 14 , 15 ]. Recent studies found that lncRNAs single-nucleotide polymorphisms (SNPs) may be involved in the carcinogenesis of gastric cancer [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The possible role of different genetic alterations in the development of gastric cancer has been studied [ 13 , 14 , 15 ]. Recent studies found that lncRNAs single-nucleotide polymorphisms (SNPs) may be involved in the carcinogenesis of gastric cancer [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the expression of CCKBR is regarded as a symbol that has a close relationship with gastric canceration. IL-12β is a pro-inflammatory cytokine that is produced by various immune cells [ 86 , 87 ]. The expression of IL-12β can be remarkably increased when the inflammatory response occurs in the layer of gastric tissues [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…When some of the SNPs were in complete linkage disequilibrium (r 2 = 1), only one SNP was selected for genotyping. Finally, we included four SNPs in CCND1 (rs1944129, rs7177, rs9344 and rs678653), which were recently found to be significantly associated with some malignancies in the Chinese population [ 31 , 32 , 38 ].…”
Section: Methodsmentioning
confidence: 99%